2012
DOI: 10.1103/physrevb.85.205305
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Fano resonance of an exciton in laser-driven semiconductor superlattices

Abstract: An excitonic Floquet state in semiconductor superlattices (SLs) driven by an intense monochromatic laser is examined based on multichannel scattering theory, where this state is supported by a photon sideband attributed to a SL joint miniband. It is shown that the excitonic Fano resonance (FR) is caused by the coupling between photon sidebands, and thus one obtains the possibility of dynamic quantum control of this exciton state by means of laser tuning. This FR differs from the conventional FR observed in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 52 publications
(62 reference statements)
1
16
0
Order By: Relevance
“…CROWs have been explored in a variety of material platforms and resonator types, including photonic-crystal defect cavities, microspheres, microdisks, and microring resonators [22,23], with applications to light slowing down and storage [24][25][26], light capturing [27], time reversal [28,29], sensing [30], and for the realization of topologically-protected edge states. [31] While in static CROW structures Fano resonances are usually realized by side-coupled microcavities [2,32], in our setup they arise dynamically from the interference of different Floquet channels [33][34][35][36][37][38], and can be thus controlled by tuning the frequency and amplitude of the modulation signal.…”
Section: Introductionmentioning
confidence: 99%
“…CROWs have been explored in a variety of material platforms and resonator types, including photonic-crystal defect cavities, microspheres, microdisks, and microring resonators [22,23], with applications to light slowing down and storage [24][25][26], light capturing [27], time reversal [28,29], sensing [30], and for the realization of topologically-protected edge states. [31] While in static CROW structures Fano resonances are usually realized by side-coupled microcavities [2,32], in our setup they arise dynamically from the interference of different Floquet channels [33][34][35][36][37][38], and can be thus controlled by tuning the frequency and amplitude of the modulation signal.…”
Section: Introductionmentioning
confidence: 99%
“…Although a number of studies of the DWSL have been focused on its importance [49][50][51][52][53] these studies are limited to a small α region, and thus the significance of the ac-ZT interaction is overlooked to the best of our knowledge. Recently, two of the authors have demonstrated the manifestation of an asymmetric Fano lineshape of a photodressed-exciton state in interband absorption spectra, 40,41 though this study just addresses the few-body problem. Further study is in progress, taking account of the many-body effect within the mean-field approximation based on the semiconductor-Bloch equations.…”
Section: Discussionmentioning
confidence: 99%
“…Further, this has been applied to the study of a more complicated excitonic Floquet problem of the DWSL. 40,41 The present study is regarded as the further developed study of Ref. 19 toward a comprehensive understanding of the DWSL with η integer.…”
mentioning
confidence: 99%
“…The first category is regarding whether a process is a linear one or a nonlinear one with respect to an order of a laser-matter interaction, as categorized as (a1) and (a2), respectively. For instance, the former is a photoabsorption process [8][9][10][11], and the latter is a multiphoton process [12][13][14][15][16]. The second category is regarding whether the process results from a built-in interaction between the discrete level and continuum that is intrinsic to a material itself or from a coupling induced extrinsically by a laser, as categorized as (b1) and (b2), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, this is whether (quasi)time-independent or timedependent. For instance, the former is induced by a continuous-wave (cw) laser (monochromatic laser) [15,16,25,26], and the latter is by a short pulsed laser [27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%